Diagnostic Criteria in Neurology - Lerner, Alan J.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2006)
Accurate diagnosis, the best way to avoid inadequate and inappropriate patient treatment, is the first and foremost responsibility of the physician. In Diagnostic Criteria in Neurology, Alan J. Lerner, MD, seeks to codify the diagnostic process by compiling sets of previously published diagnostic criteria for a diverse group of neurological conditions. The criteria are derived from the best currently available medical sources and reflect the great variety of possible standards that have been proposed. They cover a wide spectrum of neurological conditions whose diagnosis does not depend solely on histopathology (e.g., brain tumors), including cerebrovascular diseases, dementias and behavioral disorders, demyelinating disorders, and disorders of consciousness and brain death. Standardized criteria are also provided for epilepsy, genetic syndromes, headache, immune-based disorders, infectious diseases, movement disorders, neuromuscular disorders, and sleep disorders. A dazzling array of tables summarize useful information on both common and uncommon neurological conditions, including many genetic and pediatric neurological disorders. A companion personal digital assistant (PDA) version (1-58829-854-X), sold separately, is available from the Humana Press website (www.humanapress.com) for easy downloading and use on the reader's PDA. Innovative and authoritative, Diagnostic Criteria in Neurology begins to do for neurology what the DSM (Diagnostic and Statistical Manual) did for psychiatry: provide practicing neurologists and neurological residents with handy access to the latest published diagnostic criteria for successfully treating their patients.
Consensus, Disagreement, and Diagnostic Labels -- Cerebrovascular Diseases -- Dementias and Behavioral Disorders -- Demyelinating Disorders -- Disorders of Consciousness and Brain Death -- Epilepsy -- Genetic Syndromes -- Headache -- Immune-Based Disorders -- Infectious Diseases -- Movement Disorders -- Neuromuscular Disorders -- Pain, Fatigue, and Trauma -- Sleep Disorders.
Keywords: Medicine; Neurology; Medicine & Public Health; Neurology; Electronic books